Groundwater management in the face of climate change: enhancing groundwater storage in the alluvium aquifer of Wadi Araba, Jordan, through GIS-based managed aquifer recharge and groundwater MODFLOW - Ala’ Alelaimat; Ismail Yusoff; Mohd Khairul Nizar; Tham Fatt Ng; Yahya A. Majali (Water Supply, 2023)
Groundwater is critical in countries such as Jordan, yet demand exceeds availability due to population expansion and arid conditions. The goal of this research is to address water scarcity and adapt to reduced rainfall by investigating the soil aquifer and evaluating the efficiency of managed aquifer recharge (MAR). The Wadi Araba Basin's alluvium aquifer is particularly important and contains a groundwater divide, with water flowing towards the Red Sea to the south and the Dead Sea to the north, as determined by rigorous modelling and scenario analysis. Precipitation infiltration is an important consideration in groundwater budget modelling. This study employs 12 monitoring wells to establish an acceptable relationship between estimated and observed water levels. Furthermore, the study creates a MAR suitability map, which evaluates eight potential MAR locations in the Wadi Araba region. According to forecasted scenarios, implementing MAR in conjunction with increased precipitation recharge has the potential to ameliorate the consequences of decreased rainfall in the model region. The plan aims to raise the water table in three areas by 1.96–3.12%, providing realistic solutions to enhance water availability and adapt to climate change. HIGHLIGHTS Groundwater plays a crucial role in addressing water scarcity.; Research in Wadi Araba Basin evaluating Managed Aquifer Recharge strategy to combat water scarcity.; The potential to raise the water table by 1.16% in specific areas.; Focusing on conductivity values to generate a calibration curve.; The level chart of the basin revealed ground water divided in alluvium aquifer water flows in two directions.;